Perbandingan Respons Antibodi setelah Vaksinasi COVID-19 antara Individu dengan dan tanpa Komorbiditas - Bella, Isa; Khariri, Khariri; Hartanti, Monica Dwi; Sisca, Sisca; Thabit, Jihan Samira; Effendi, Ida; Devita, Arleen; Robertus, Thomas (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Vaccination is a Crucial public health strategy for reducing the transmission of viral infections and protecting populations from severe illness. COVID-19 vaccines have played a significant role in decreasing the incidence and mortality rates linked to the virus. However, immune responses to vaccination may differ among individuals, especially those with comorbidies that could alter immune function. This study aimed to compare antibody responses in adults with and without comorbidities, 18 months after receiving the COVID-19 vaccine. Methods This was a cohort study with two sampling time points: before vaccination and 18 months after vaccination. The study was conducted in Yogyakarta, Indonesia. Data were collected through self-administered questionnaires and venous blood sampling. Antibody titers were measured to evaluate the humoral immune response in participants with and without comorbidities. Results Before vaccination, the highest proportion of positive antibody titers was found among females (40.2%), individuals aged 18–44 years (44.7%), those with a senior high school education (48.1%), and individuals with normal body weight (44.3%). A Comparison of antibody levels at baseline and 18 months after vaccination between groups with and without comorbidities showed no statistically significant difference, with a p-value of 0.992. Conclusions Although no significant difference was found in antibody responses between individuals with and without comorbidities, comorbid conditions may still influence immune response depending on their type and severity. These findings suggest the need for further research to examine the specific effects of various comorbidities on long-term vaccine-induced immunity.